2022
DOI: 10.3390/curroncol29120775
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C-Reactive Protein-to-Albumin Ratio Predicts Postoperative Pancreatic Fistula following Pancreatoduodenectomy: A Single-Center, Retrospective Study

Abstract: Postoperative pancreatic fistula (POPF) following pancreatoduodenectomy (PD) is a potentially lethal complication, and it is clinically important to determine its risk preoperatively. Although C-reactive protein-to-albumin ratio (CAR) is reported to be a prognostic marker for postoperative complications in several cancers, no evidence is currently available regarding the association between preoperative CAR and POPF following PD for periampullary tumors. This study examined whether preoperative CAR could predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Therefore, we assumed that indicators encompassing both the nutritional status and inflammatory conditions would be more promising. Various indicators, including the lymphocyte-to-CRP ratio [ 34 ], platelet-to-albumin ratio [ 35 ], neutrophil-to-lymphocyte ratio [ 36 , 37 ], platelet-to-lymphocyte ratio [ 38 ], prognostic nutritional index [ 39 , 40 ], and CAR [ 41 , 42 ], which take into account both inflammation and nutritional status, have been identified as predictors of prognosis or POCs. Among these indicators, the identification of one as a useful prognostic marker may also allow us to predict the S-1 completion rates for AC, which are correlated with better prognosis in PC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we assumed that indicators encompassing both the nutritional status and inflammatory conditions would be more promising. Various indicators, including the lymphocyte-to-CRP ratio [ 34 ], platelet-to-albumin ratio [ 35 ], neutrophil-to-lymphocyte ratio [ 36 , 37 ], platelet-to-lymphocyte ratio [ 38 ], prognostic nutritional index [ 39 , 40 ], and CAR [ 41 , 42 ], which take into account both inflammation and nutritional status, have been identified as predictors of prognosis or POCs. Among these indicators, the identification of one as a useful prognostic marker may also allow us to predict the S-1 completion rates for AC, which are correlated with better prognosis in PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to a large-scale study, patients who experienced severe POCs, specifically those with a CD grade ≥3, were reported to initiate AC less frequently after pancreatic surgery [ 50 ]. Furthermore, it has been demonstrated that CAR serves as a valuable predictor of POCs following pancreatic resection [ 41 , 42 ]. CAR, a straightforward metric calculated solely through blood tests, has been underscored as a prognostic factor for PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…CAR was estimated using preoperative CRP and serum albumin values. These data were obtained preoperatively and calculated using the following formula: CAR = CRP (mg/dL) / Serum albumin (g/dL) [ 9 ].…”
Section: Methodsmentioning
confidence: 99%